2021
DOI: 10.1186/s12876-021-02044-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of human astrovirus and sapovirus in outpatients with acute gastroenteritis in Guangzhou, China

Abstract: Background Human astrovirus (HAstV) and sapovirus (SaV) are common pathogens that can cause acute gastroenteritis (AGE). However, very few studies have reported the molecular epidemiology and clinical information on HAstV and SaV in China. This study aims to determine the molecular epidemiology and clinical features of HAstV and SaV in patients with AGE in Guangzhou, China. Methods For this study, 656 patients with AGE were enrolled. Their stool sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
4
2
2
Order By: Relevance
“…The findings from this study indicate that HuSaV was the second most prevalent cause of AGE outbreaks, following NoV, in the Chaoyang District of Beijing, China, between 2015 and 2021, which is consistent with observations in some other countries ( 6 - 7 ). Nonetheless, the genetic diversity of HuSaV found in this study differs from previous reports in both China ( 8 - 9 ) and other countries ( 10 - 13 ), where the GI genogroup was predominant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings from this study indicate that HuSaV was the second most prevalent cause of AGE outbreaks, following NoV, in the Chaoyang District of Beijing, China, between 2015 and 2021, which is consistent with observations in some other countries ( 6 - 7 ). Nonetheless, the genetic diversity of HuSaV found in this study differs from previous reports in both China ( 8 - 9 ) and other countries ( 10 - 13 ), where the GI genogroup was predominant.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other reports on the seasonal distribution of HuSaVs, outbreaks in Beijing typically take place during two periods, as depicted in Figure 1 . This variation significantly differs from the early spring occurrences reported in southern China ( 9 ), which may result from the considerable difference in latitudes between the two regions. In Japan, researchers have also discovered that the detection rate of HuSaV within a month varied across different years ( 6 ).…”
Section: Discussioncontrasting
confidence: 86%
“…We conducted a 6-consecutive-year monitoring and epidemiology study of HAdV in association with acute gastroenteritis from January 2015 to December 2021 to assess HAdV prevalence and to examine the genetic characteristics of viruses obtained from hospitalized children with acute diarrhea. HAdV was detected in 72 samples from these patients, and the detection rate was 4.10%, which is similar to the rates reported previously in Shanghai [ 9 ], Guangzhou [ 17 ], and China as a whole [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…Human enteric adenovirus F40/41 was a major cause of acute gastroenteritis in children in Brazil from 2018 to 2020 [ 11 ]. In China, among patients with acute gastroenteritis, HAdV-F41 has been reported to be the predominant type, followed by HAdV species B and C [ 17 ]. In the current study of HAdV in Yunnan province, 13 strains were sequenced, 10 of which were HAdV-F41 (76.92%) and three of which were HAdV-C2 (23.08%), HAdV-F40 and other types were not found, presumably because of the small number of sequences analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al. 9 reported that rotavirus remained the primary viral pathogen followed by norovirus among outpatient children with AGE in Guangzhou, China. However, comprehensive investigations encompassing a wide range of pathogens including both bacteria and viruses are rarely reported for AGE patients.…”
Section: Introductionmentioning
confidence: 99%